VEGF111: new insights in tissue invasion - Danastas, Kevin; Combes, Valery; Lindsay, Laura A.; Grau, Georges E. R.; Thompson, Michael B.; Murphy, Christopher R. (Frontiers in Physiology, 2015)
Vascular endothelial growth factor is a secreted glycoprotein that acts on endothelial cells to induce developmental and physiological angiogenesis. It has also been implicated in angiogenesis occurring in several pathologies, most notably, cancer. Alternative splicing of VEGF mRNA transcripts results in several isoforms with distinct properties depending on their exon composition. Recently, a new isoform has been identified, VEGF111 with a unique exon composition responsible for its high angiogenic potential. In humans, the only known inducer of VEGF111 is DNA damage but its natural presence in the uterus of the viviparous lizard, Saiphos equalis, suggests other mechanisms of regulation. Most interestingly, the possible relationship between the evolution of viviparity and the associated increased risk in developing cancer may be important in understanding the mechanisms underlying tumor development.